Bisphosphonate-induced zebra lines in fibrous dysplasia of bone: histo-radiographic correlation in a case of McCune Albright-Syndrome - Corsi, Alessandro (Skeletal Radiol, 2017)
Bisphosphonates (BPs) are currently used in the treatment of diverse bone diseases including fibrous dysplasia of bone (FD). In pediatric patients, a radiographic consequence of cyclical administration of BPs is the development of apo-, epi-, and meta-physeal sclerotic bands, otherwise known as zebra lines, which result from the temporary inhibition of osteoclastic activity at the time of drug treatment. We report here on a child with McCune–Albright syndrome (FD in addition to hyperfunctioning endocrinopathies and skin hyperpigmentation) treated with cyclical intravenous infusions of pamidronate in which conventional radiography, contact microradiography, histology, and backscattered electron image analysis demonstrated that zebra lines formed only where bone was normal, were arrested at the boundary between FD-unaffected and FD-affected bone where bone is sclerotic, and were absent within the undermineralized FD bone. Moreover, in spite of the treatment, the FD lesions continued to expand. This case report is unique because no previously published studies correlated the radiographic and the histologic features of BP-induced zebra lines in the metaphysis of an FD-affected long bone of the limbs.